Pouring method for coke oven top platform

By using a two-layer castable material composite and metal-reinforced grid frame on the top platform of the coke oven, the problem of through-crack cracks caused by sun exposure, furnace temperature, rainwater and vibration of refractory bricks is solved, and the infiltration of rainwater is prevented and The effect of improving the load-bearing capacity of the furnace roof platform.

CN119432406APending Publication Date: 2025-02-14WUXI BAOZHAN ENERGY SAVING MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444311.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Under the influence of factors such as sun exposure, furnace temperature leakage, rainwater quench and heavy pressure vibration of the material truck, the refractory bricks on the top platform gradually appear through cracks, causing rainwater to seep into the furnace body, affecting the stability and normal production of the coke oven furnace. .

Method used

Use two layers of castables to combine, use new castables with low thermal conductivity and high strength in the light layer, use mullite castables with good thermal shock performance and high strength in the heavy layer, and add them between the two layers. Metal reinforced grid frames to disperse load-bearing forces and increase interlayer bonding strength.

Benefits of technology

Effectively prevent rainwater from seeping into the furnace body, reduce the furnace top surface temperature, and improve the overall load-bearing capacity of the coke oven furnace top platform and the service life of the refractory material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432406A_ABST
    Figure CN119432406A_ABST
Patent Text Reader

Abstract

The invention discloses a coke oven top platform pouring method, which comprises the following steps: carrying out light layer construction: pouring a No.2 pouring material into a construction part, vibrating the construction part by adopting a vibrating bar to remove air holes, enabling the thickness of the thinnest part to be not less than 70mm, and then trowelling; a metal reinforced grid frame is added, specifically, the metal reinforced grid frame is flatly laid on the surface of the trowelled second castable; after the light layer is hardened, a first castable is poured into the surface of the tiled metal reinforced grid frame, the water adding amount is 7-10% of the mass of the first castable, a vibrating spear is adopted for vibration compaction, and screeding is conducted after the needed construction thickness is achieved; and curing: spraying water every 1 hour for wetting, and curing at normal temperature for more than 24 hours. The invention has the innovation point that two layers of castable are compounded for use and are applied to the coke oven top to prevent rainwater from permeating into the oven body to influence the production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coke oven top casting, in particular to a coke oven top platform casting method. Background Art

[0002] The coke oven roof platform is an important part of the coke oven production process. It is located on the top of the coke oven and is mainly used to support the roof equipment, such as the riser, bridge pipe, water seal valve, etc. These equipment play an important role in the coke oven production. The platform also provides a place for operators to perform related operations, such as checking the furnace condition, adjusting the furnace temperature, and dealing with problems such as smoke on the furnace roof.

[0003] The original coke oven roof platform, except for the main structural joints, is built with refractory bricks on the main plane. It is exposed outdoors during use. The refractory brick seams gradually widen and develop into through cracks due to frequent sunlight, furnace temperature penetration, rainwater rapid cooling, and vibration caused by the heavy pressure of the material car. Rainwater backflow has a serious adverse effect on the stability of the coke oven temperature and normal production. Summary of the invention

[0004] The purpose of the invention is to provide a method for pouring a coke oven top platform.

[0005] The innovation of the present invention lies in the composite use of two layers of castables, which are applied to the top of the coke oven to prevent rainwater from penetrating into the furnace body and affecting production.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is: A method for casting a coke oven roof platform, characterized in that it comprises the following steps: (1) Take heavy raw materials, which include No. 1 fine powder, binder, water reducer, organic fiber, No. 1 aggregate and stainless steel heat-resistant fiber. No. 1 fine powder includes white corundum fine powder, alumina ultrafine powder and high-purity silicon powder. No. 1 aggregate includes fused synthetic mullite with a particle size of >5mm and <8mm, fused synthetic mullite with a particle size of >1mm and <3mm, and fused synthetic mullite with a particle size of <1mm. The weight percentages of the heavy raw materials are: white corundum fine powder 16-18%, alumina ultrafine powder 16-18%, Fine powder 3~4%, high-purity silicon powder 3~4%, binder 5~7%, water reducer 0.15~0.2%, organic fiber 0.08~0.1%, fused synthetic mullite with particle size >5mm and <8mm 8~10%, fused synthetic mullite with particle size >3mm and <5mm 16~17%, fused synthetic mullite with particle size >1mm and <3mm 20~21%, fused synthetic mullite with particle size <1mm 23~25%, stainless steel heat-resistant fiber 1~1.5%; (2) First, the No. 1 fine powder, binder, water reducing agent and organic fiber are uniformly mixed to obtain a No. 1 premix; (3) Adding aggregate No. 1 to premix No. 1 and mixing evenly to obtain premix No. 2; (4) adding stainless steel heat-resistant fiber to the No. 2 premix and mixing evenly to obtain a No. 3 premix; (5) Add water to the No. 3 premix and stir evenly to obtain the No. 1 castable. The amount of water added is 6-9% of the mass of the No. 3 premix; (6) Weighing a porous light mullite particle raw material, the porous light mullite particle raw material comprises mullite fine powder, silicon powder, alumina fine powder, fly ash, kaolin, PP particles with a particle size of 1-5 mm, a foaming agent, and 6 mm organic fiber, wherein the mass percentage of the porous light mullite particle raw material is as follows: the porous light mullite particle raw material comprises 26-40% of mullite fine powder, 10-16% of silicon powder, 20-34% of alumina fine powder, 8-12% of fly ash, 8-12% of kaolin, 5% of PP particles with a particle size of 1-5 mm, 1% of foaming agent, and 0.1-0.15% of 6 mm organic fiber; adding water to the porous light mullite particle raw material, stirring evenly, and pressing into blocks, wherein the amount of water added is 3-5% of the mass of the porous light mullite particle raw material, sintering at 1250° C. and re-crushing into porous light mullite particles; (7) Take lightweight raw materials: including No. 2 aggregate, No. 2 fine powder, binder, and water reducer. No. 2 aggregate includes porous lightweight mullite particles with a particle size of >5mm and <8mm, porous lightweight mullite particles with a particle size of >3mm and <5mm, porous lightweight mullite particles with a particle size of >1mm and <3mm, hollow alumina spheres with a particle size of >1mm and <3mm, and lightweight mullite with a particle size of <1mm. No. 2 fine powder includes synthetic mullite fine powder, alumina fine powder with an alumina content of 85%, and high-purity silicon powder. The weight percentage of the lightweight raw materials is: 5-10% porous light mullite particles with a particle size of >3mm and <5mm, 15-17% porous light mullite particles with a particle size of >3mm and <5mm, 10% porous light mullite particles with a particle size of >1mm and <3mm, 8-10% alumina hollow spheres with a particle size of >1mm and <3mm, 20-22% light mullite with a particle size of <1mm, 8-10% mullite fine powder, 12-15% alumina fine powder with an alumina content of 85%, 3-5% high-purity silicon powder, 8-12% binder, and 0.15-0.2% water reducer, and mix them evenly to obtain No. 4 premix; (8) Add water to the No. 4 premix and stir evenly to obtain the No. 2 castable. The amount of water added is 20-25% of the mass of the No. 3 premix; (9) Carry out lightweight layer construction: Pour No. 2 castable into the construction site, vibrate the construction site with a vibrating rod to remove air holes, and the thickness of the thinnest part should not be less than 70 mm, and then smooth it; (10) Adding metal reinforced grid frame: Lay the metal reinforced grid frame flat on the smooth surface of No. 2 castable; (11) Construction of heavy layer: After the light layer hardens, pour No. 1 castable onto the surface of the flat metal reinforced grid frame, add 7-10% of the mass of No. 1 castable with water, use a vibrating rod to vibrate and compact, and smooth it after reaching the required construction thickness; (12) Maintenance: Sprinkle water every hour to keep it moist, and maintain at room temperature for more than 24 hours.

[0007] Furthermore, the binder is high alumina cement.

[0008] Furthermore, the water reducer is a phosphate water reducer or a naphthalene water reducer.

[0009] Furthermore, the metal reinforced grid frame is connected by four metal sheets in a tic-tac-toe structure, and the tic-tac-toe structure is connected by S-shaped nails. The metal sheets are arranged horizontally and the S-shaped nails are arranged vertically.

[0010] Furthermore, the metal sheet and the S-shaped nail are both made of 06Cr23Ni13 stainless steel.

[0011] The beneficial effects of the present invention are: 1. The present invention adopts two layers of castables for composite use and is applied to the coke oven roof to prevent rainwater from penetrating into the furnace body and affecting production; the layers of the new composite castable have different functions, the light layer adopts a new castable with low thermal conductivity and higher strength than ordinary light castables, which can reduce the surface temperature of the platform without affecting the load-bearing capacity of the platform; the heavy layer adopts a corundum mullite castable with good thermal shock resistance, high strength and stable volume; a metal reinforced grid frame is newly added between the light layer and the heavy layer, so that the surface load will not damage the light layer due to local concentration, and the layers are mutually integrated and promoted, which greatly improves the service life of the refractory material of the coke oven roof platform and ensures that the outdoor roof will not leak rainwater due to factors such as regional seasons.

[0012] 2. During the multi-layer pouring construction in the present invention, a newly designed interlayer metal grid frame is added above the lightweight layer. The material is 06Cr23Ni13 heat-resistant stainless steel. Its function is to disperse the bearing force of the outer layer of the platform to the lower layer of lightweight castables, increase the interlayer bonding strength, solve the problem of relatively weak strength of the lightweight layer, and improve the overall bearing capacity of the coke oven top platform. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic diagram of the structure of the present invention.

[0014] Figure 2 Schematic diagram of the structure of the metal reinforced grid frame.

[0015] Figure 3 A cross-sectional view of a metal reinforced grid frame. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings.

[0017] Embodiment 1: A method for casting a coke oven roof platform, comprising the following steps: (1) Take heavy raw materials, which include No. 1 fine powder, binder, water reducer, organic fiber, No. 1 aggregate and stainless steel heat-resistant fiber. No. 1 fine powder includes white corundum fine powder, alumina ultrafine powder and high-purity silicon powder. No. 1 aggregate includes fused synthetic mullite with a particle size of >5mm and <8mm, fused synthetic mullite with a particle size of >1mm and <3mm, and fused synthetic mullite with a particle size of <1mm. The weight percentages of the heavy raw materials are: white corundum fine powder 18%, alumina ultrafine powder, high-purity silicon ... Ultrafine aluminum powder 3%, high-purity silicon powder 3%, binder 7%, water reducer 0.15%, organic fiber 0.08%, fused synthetic mullite with particle size >5mm and <8mm 8.77%, fused synthetic mullite with particle size >3mm and <5mm 16%, fused synthetic mullite with particle size >1mm and <3mm 20%, fused synthetic mullite with particle size <1mm 23%, stainless steel heat-resistant fiber 1%; binder is high-aluminum cement; water reducer is phosphate water reducer; (2) First, the No. 1 fine powder, binder, water reducing agent and organic fiber are uniformly mixed to obtain a No. 1 premix; (3) Adding aggregate No. 1 to premix No. 1 and mixing evenly to obtain premix No. 2; (4) adding stainless steel heat-resistant fiber to the No. 2 premix and mixing evenly to obtain a No. 3 premix; (5) Add water to the No. 3 premix and stir evenly to obtain the No. 1 castable. The amount of water added is 6% of the mass of the No. 3 premix; (6) Weighing a porous light mullite particle raw material, the porous light mullite particle raw material includes mullite fine powder, silicon powder, alumina fine powder, fly ash, kaolin, PP particles with a particle size of 1-5 mm, a foaming agent, and 6 mm organic fiber, wherein the mass percentage of the porous light mullite particle raw material is as follows: the porous light mullite particle raw material includes 26% of mullite fine powder, 10% of silicon powder, 34% of alumina fine powder, 11.85% of fly ash, 12% of kaolin, 5% of PP particles with a particle size of 1-5 mm, 1% of foaming agent, and 0.15% of 6 mm organic fiber; adding water to the porous light mullite particle raw material, stirring evenly, and pressing into blocks, wherein the amount of water added is 3% of the mass of the porous light mullite particle raw material, sintering at 1250° C. and re-crushing into porous light mullite particles; (7) Take lightweight raw materials: including No. 2 aggregate, No. 2 fine powder, binder, and water reducer. No. 2 aggregate includes porous lightweight mullite particles with a particle size of >5mm and <8mm, porous lightweight mullite particles with a particle size of >3mm and <5mm, porous lightweight mullite particles with a particle size of >1mm and <3mm, hollow alumina spheres with a particle size of >1mm and <3mm, and lightweight mullite with a particle size of <1mm. No. 2 fine powder includes synthetic mullite fine powder, alumina fine powder with an alumina content of 85%, and high-purity silicon powder. The weight percentage of the lightweight raw materials is: 10% porous light mullite particles with a particle size of mm and <8mm, 15% porous light mullite particles with a particle size of >3mm and <5mm, 10% porous light mullite particles with a particle size of >1mm and <3mm, 8% alumina hollow spheres with a particle size of >1mm and <3mm, 20% light mullite with a particle size of <1mm, 8% mullite fine powder, 12% alumina fine powder with an alumina content of 85%, 3% high-purity silicon powder, 12% binder, and 0.15% water reducer are mixed evenly to obtain No. 4 premix; the binder is high alumina cement; the water reducer is phosphate water reducer; (8) Add water to the No. 4 premix and stir evenly to obtain the No. 2 castable. The amount of water added is 20% of the mass of the No. 3 premix. (9) Carry out lightweight layer construction: Pour No. 2 castable into the construction site, vibrate the construction site with a vibrating rod to remove air holes, the thickness of the thinnest part is 70mm, and then smooth it; (10) Adding metal reinforced grid frame: The metal reinforced grid frame is laid flat on the smoothed surface of No. 2 castable; the metal reinforced grid frame is connected by four metal sheets in a tic-tac-toe structure, and the tic-tac-toe structure is connected by S-shaped nails. The metal sheets are arranged horizontally and the S-shaped nails are arranged vertically; the materials of the metal sheets and the S-shaped nails are both 06Cr23Ni13 stainless steel.

[0018] (11) Construction of heavy layer: After the light layer hardens, pour No. 1 castable onto the surface of the flat metal reinforced grid frame, add 7% of the mass of No. 1 castable with water, vibrate with a vibrating rod to compact, and smooth after reaching the required construction thickness; (12) Maintenance: Sprinkle water every hour to keep it moist, and maintain at room temperature for 24 hours.

[0019] Embodiment 2: A method for casting a coke oven top platform, comprising the following steps: (1) Take heavy raw materials, which include No. 1 fine powder, binder, water reducer, organic fiber, No. 1 aggregate and stainless steel heat-resistant fiber. No. 1 fine powder includes white corundum fine powder, ultrafine alumina powder and high-purity silicon powder. No. 1 aggregate includes fused synthetic mullite with a particle size of >5mm and <8mm, fused synthetic mullite with a particle size of >1mm and <3mm, and fused synthetic mullite with a particle size of <1mm. The weight percentages of the heavy raw materials are: 16% white corundum fine powder, 16% alumina powder, and 16% Ultrafine aluminum powder 4%, high-purity silicon powder 4%, binder 5.1%, water reducer 0.2%, organic fiber 0.1%, fused synthetic mullite with particle size >5mm and <8mm 8%, fused synthetic mullite with particle size >3mm and <5mm 17%, fused synthetic mullite with particle size >1mm and <3mm 21%, fused synthetic mullite with particle size <1mm 23.1%, stainless steel heat-resistant fiber 1.5%; binder is high-alumina cement; water reducer is naphthalene-based water reducer; (2) First, the No. 1 fine powder, binder, water reducing agent and organic fiber are uniformly mixed to obtain a No. 1 premix; (3) Adding aggregate No. 1 to premix No. 1 and mixing evenly to obtain premix No. 2; (4) adding stainless steel heat-resistant fiber to the No. 2 premix and mixing evenly to obtain a No. 3 premix; (5) Add water to the No. 3 premix and stir evenly to obtain the No. 1 castable. The amount of water added is 7% of the mass of the No. 3 premix; (6) Weighing a porous light mullite particle raw material, the porous light mullite particle raw material includes mullite fine powder, silicon powder, alumina fine powder, fly ash, kaolin, PP particles with a particle size of 1-5 mm, a foaming agent, and 6 mm organic fiber, wherein the mass percentage of the porous light mullite particle raw material is as follows: the porous light mullite particle raw material includes 40% of mullite fine powder, 16% of silicon powder, 20% of alumina fine powder, 8% of fly ash, 9.9% of kaolin, 5% of PP particles with a particle size of 1-5 mm, 1% of foaming agent, and 0.1% of 6 mm organic fiber; adding water to the porous light mullite particle raw material, stirring evenly, and pressing into blocks, wherein the amount of water added is 4% of the mass of the porous light mullite particle raw material, sintering at 1250° C. and re-crushing into porous light mullite particles; (7) Take lightweight raw materials: including No. 2 aggregate, No. 2 fine powder, binder, and water reducer. The No. 2 aggregate includes porous lightweight mullite particles with a particle size of >5mm and <8mm, porous lightweight mullite particles with a particle size of >3mm and <5mm, porous lightweight mullite particles with a particle size of >1mm and <3mm, hollow alumina spheres with a particle size of >1mm and <3mm, and lightweight mullite with a particle size of <1mm. The No. 2 fine powder includes synthetic mullite fine powder, alumina fine powder with an alumina content of 85%, and high-purity silicon powder. The weight percentage of the lightweight raw materials is: 5% porous light mullite particles with a size of 5mm and less than 8mm, 15% porous light mullite particles with a particle size of >3mm and <5mm, 10% porous light mullite particles with a particle size of >1mm and <3mm, 9.8% alumina hollow spheres with a particle size of >1mm and <3mm, 22% light mullite with a particle size of <1mm, 10% mullite fine powder, 15% alumina fine powder with an alumina content of 85%, 5% high-purity silicon powder, 8% binder, and 0.2% water reducer are uniformly mixed to obtain No. 4 premix; the binder is high alumina cement; the water reducer is a naphthalene-based water reducer; (8) Add water to the No. 4 premix and stir evenly to obtain the No. 2 castable. The amount of water added is 22% of the mass of the No. 3 premix. (9) Carry out lightweight layer construction: Pour No. 2 castable into the construction site, vibrate the construction site with a vibrating rod to remove air holes, the thickness of the thinnest part is 80mm, and then smooth it; (10) Adding metal reinforced grid frame: The metal reinforced grid frame is laid flat on the smoothed surface of No. 2 castable; the metal reinforced grid frame is connected by four metal sheets in a tic-tac-toe structure, and the tic-tac-toe structure is connected by S-shaped nails. The metal sheets are arranged horizontally and the S-shaped nails are arranged vertically; the materials of the metal sheets and the S-shaped nails are both 06Cr23Ni13 stainless steel.

[0020] (11) Construction of heavy layer: After the light layer hardens, pour No. 1 castable onto the surface of the flat metal reinforced grid frame, add water in an amount of 8% of the mass of No. 1 castable, vibrate and compact with a vibrating rod, and smooth it after reaching the required construction thickness; (12) Maintenance: Sprinkle water every hour to keep it moist, and maintain at room temperature for 26 hours.

[0021] Embodiment 3: A method for casting a coke oven roof platform, comprising the following steps: (1) Take heavy raw materials, which include No. 1 fine powder, binder, water reducer, organic fiber, No. 1 aggregate and stainless steel heat-resistant fiber. No. 1 fine powder includes white corundum fine powder, alumina ultrafine powder and high-purity silicon powder. No. 1 aggregate includes fused synthetic mullite with a particle size of >5mm and <8mm, fused synthetic mullite with a particle size of >1mm and <3mm, and fused synthetic mullite with a particle size of <1mm. The weight percentages of the heavy raw materials are: white corundum fine powder 16.1%, alumina ultrafine powder 16.2%, 3.1% powder, 3.1% high-purity silica powder, 5% binder, 0.16% water reducer, 0.09% organic fiber, 10% fused synthetic mullite with a particle size of >5mm and <8mm, 16.2% fused synthetic mullite with a particle size of >3mm and <5mm, 20.15% fused synthetic mullite with a particle size of >1mm and <3mm, 25% fused synthetic mullite with a particle size of <1mm, and 1.1% stainless steel heat-resistant fiber; the binder is high alumina cement; the water reducer is phosphate water reducer; (2) First, the No. 1 fine powder, binder, water reducing agent and organic fiber are uniformly mixed to obtain a No. 1 premix; (3) Adding aggregate No. 1 to premix No. 1 and mixing evenly to obtain premix No. 2; (4) adding stainless steel heat-resistant fiber to the No. 2 premix and mixing evenly to obtain a No. 3 premix; (5) Add water to the No. 3 premix and stir evenly to obtain the No. 1 casting material. The amount of water added is 8% of the mass of the No. 3 premix; (6) Weighing a porous light mullite particle raw material, the porous light mullite particle raw material includes mullite fine powder, silicon powder, alumina fine powder, fly ash, kaolin, PP particles with a particle size of 1-5 mm, a foaming agent, and 6 mm organic fiber, wherein the mass percentage of the porous light mullite particle raw material is as follows: the porous light mullite particle raw material includes 35.88% of mullite fine powder, 13% of silicon powder, 25% of alumina fine powder, 12% of fly ash, 8% of kaolin, 5% of PP particles with a particle size of 1-5 mm, 1% of foaming agent, and 0.12% of 6 mm organic fiber; adding water to the porous light mullite particle raw material, stirring evenly, and pressing into blocks, wherein the amount of water added is 4.5% of the mass of the porous light mullite particle raw material, sintering at 1250° C. and re-crushing into porous light mullite particles; (7) Take lightweight raw materials: including No. 2 aggregate, No. 2 fine powder, binder, and water reducer. The No. 2 aggregate includes porous lightweight mullite particles with a particle size of >5mm and <8mm, porous lightweight mullite particles with a particle size of >3mm and <5mm, porous lightweight mullite particles with a particle size of >1mm and <3mm, hollow alumina spheres with a particle size of >1mm and <3mm, and lightweight mullite with a particle size of <1mm. The No. 2 fine powder includes synthetic mullite fine powder, alumina fine powder with an alumina content of 85%, and high-purity silicon powder. The weight percentage of the lightweight raw materials is: 8mm porous lightweight mullite particles 7%, porous lightweight mullite particles with a particle size of >3mm and <5mm 17%, porous lightweight mullite particles with a particle size of >1mm and <3mm 10%, alumina hollow spheres with a particle size of >1mm and <3mm 10%, lightweight mullite with a particle size of <1mm 21%, mullite fine powder 9%, alumina fine powder with an alumina content of 85% 13%, high-purity silicon powder 4%, binder 8.82%, water reducer 0.18%, after uniform mixing to obtain No. 4 premix; the binder is high alumina cement; the water reducer is phosphate water reducer or naphthalene water reducer; (8) Add water to the No. 4 premix and stir evenly to obtain the No. 2 castable. The amount of water added is 24% of the mass of the No. 3 premix. (9) Carry out lightweight layer construction: Pour No. 2 castable into the construction site, vibrate the construction site with a vibrating rod to remove air holes, the thickness of the thinnest part is 85mm, and then smooth it; (10) Adding metal reinforced grid frame: The metal reinforced grid frame is laid flat on the smoothed surface of No. 2 castable; the metal reinforced grid frame is connected by four metal sheets in a tic-tac-toe structure, and the tic-tac-toe structure is connected by S-shaped nails. The metal sheets are arranged horizontally and the S-shaped nails are arranged vertically; the materials of the metal sheets and the S-shaped nails are both 06Cr23Ni13 stainless steel.

[0022] (11) Construction of heavy layer: After the light layer hardens, pour No. 1 castable onto the surface of the flat metal reinforced grid frame, add water in an amount of 9% of the mass of No. 1 castable, vibrate and compact with a vibrating rod, and smooth it after reaching the required construction thickness; (12) Maintenance: Sprinkle water every hour to keep it moist, and maintain at room temperature for 28 hours.

[0023] Embodiment 4: A method for casting a coke oven top platform, comprising the following steps: (1) Take heavy raw materials, which include No. 1 fine powder, binder, water reducer, organic fiber, No. 1 aggregate and stainless steel heat-resistant fiber. No. 1 fine powder includes white corundum fine powder, alumina ultrafine powder and high-purity silicon powder. No. 1 aggregate includes fused synthetic mullite with a particle size of >5mm and <8mm, fused synthetic mullite with a particle size of >1mm and <3mm, and fused synthetic mullite with a particle size of <1mm. The weight percentages of the heavy raw materials are: 17% white corundum fine powder, 17% alumina ultrafine powder and 17% 3.5%, high-purity silica powder 3.5%, binder 6%, water reducer 0.17%, organic fiber 0.08%, fused synthetic mullite with particle size >5mm and <8mm 8%, fused synthetic mullite with particle size >3mm and <5mm 16.45%, fused synthetic mullite with particle size >1mm and <3mm 20.1%, fused synthetic mullite with particle size <1mm 24%, stainless steel heat-resistant fiber 1.2%; the binder is high alumina cement; the water reducer is phosphate water reducer; (2) First, the No. 1 fine powder, binder, water reducing agent and organic fiber are uniformly mixed to obtain a No. 1 premix; (3) Adding aggregate No. 1 to premix No. 1 and mixing evenly to obtain premix No. 2; (4) adding stainless steel heat-resistant fiber to the No. 2 premix and mixing evenly to obtain a No. 3 premix; (5) Add water to the No. 3 premix and stir evenly to obtain the No. 1 castable. The amount of water added is 9% of the mass of the No. 3 premix; (6) Weighing a porous light mullite particle raw material, the porous light mullite particle raw material includes mullite fine powder, silicon powder, alumina fine powder, fly ash, kaolin, PP particles with a particle size of 1-5 mm, a foaming agent, and 6 mm organic fiber, wherein the mass percentage of the porous light mullite particle raw material is as follows: the porous light mullite particle raw material includes 31.87% of mullite fine powder, 12% of silicon powder, 30% of alumina fine powder, 10% of fly ash, 10% of kaolin, 5% of PP particles with a particle size of 1-5 mm, 1% of foaming agent, and 0.13% of 6 mm organic fiber; adding water to the porous light mullite particle raw material, stirring evenly, and pressing into blocks, wherein the amount of water added is 5% of the mass of the porous light mullite particle raw material, sintering at 1250° C. and re-crushing into porous light mullite particles; (7) Take lightweight raw materials: including No. 2 aggregate, No. 2 fine powder, binder, and water reducer. No. 2 aggregate includes porous lightweight mullite particles with a particle size of >5mm and <8mm, porous lightweight mullite particles with a particle size of >3mm and <5mm, porous lightweight mullite particles with a particle size of >1mm and <3mm, hollow alumina spheres with a particle size of >1mm and <3mm, and lightweight mullite with a particle size of <1mm. No. 2 fine powder includes synthetic mullite fine powder, alumina fine powder with an alumina content of 85%, and high-purity silicon powder. The weight percentage of the lightweight raw materials is: 8% porous light mullite particles with a particle size of >3mm and <8mm, 16% porous light mullite particles with a particle size of >3mm and <5mm, 10% porous light mullite particles with a particle size of >1mm and <3mm, 9% alumina hollow spheres with a particle size of >1mm and <3mm, 20.5% light mullite with a particle size of <1mm, 8.84% mullite fine powder, 14% alumina fine powder with an alumina content of 85%, 3.5% high-purity silicon powder, 10% binder, and 0.16% water reducer are uniformly mixed to obtain No. 4 premix; the binder is high alumina cement; the water reducer is a naphthalene-based water reducer; (8) Add water to the No. 4 premix and stir evenly to obtain the No. 2 castable. The amount of water added is 25% of the mass of the No. 3 premix. (9) Carry out lightweight layer construction: Pour No. 2 castable into the construction site, vibrate the construction site with a vibrating rod to remove air holes, the thickness of the thinnest part is 90 mm, and then smooth it; (10) Adding metal reinforced grid frame: The metal reinforced grid frame is laid flat on the smoothed surface of No. 2 castable; the metal reinforced grid frame is connected by four metal sheets in a tic-tac-toe structure, and the tic-tac-toe structure is connected by S-shaped nails. The metal sheets are arranged horizontally and the S-shaped nails are arranged vertically; the materials of the metal sheets and the S-shaped nails are both 06Cr23Ni13 stainless steel.

[0024] (11) Construction of heavy layer: After the light layer hardens, pour No. 1 castable onto the surface of the flat metal reinforced grid frame, add 10% of the mass of No. 1 castable with water, vibrate and compact with a vibrating rod, and smooth it after reaching the required construction thickness; (12) Maintenance: Sprinkle water every hour to keep it moist, and maintain at room temperature for 30 hours.

[0025] After a coking plant tried the casting method used in Examples 1 to 4, each example of the light layer had good volume stability and thermal insulation performance, and the surface temperature of the heavy layer was 30-50 degrees Celsius lower than that of the original refractory bricks. After disassembling the heavy layer, it can be seen that the light layer remains intact without cracking or damage. The light layer improves the cracking of the heavy layer after reducing the surface temperature of the furnace top, and its integrity prevents the occurrence of through cracks.

[0026] The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for casting a coke oven roof platform, characterized in that: The following steps are involved: (1) Take heavy raw materials, which include No. 1 fine powder, binder, water reducer, organic fiber, No. 1 aggregate and stainless steel heat-resistant fiber. No. 1 fine powder includes white corundum fine powder, alumina ultrafine powder and high-purity silicon powder. No. 1 aggregate includes fused synthetic mullite with a particle size of >5mm and <8mm, fused synthetic mullite with a particle size of >1mm and <3mm, and fused synthetic mullite with a particle size of <1mm. The weight percentages of the heavy raw materials are: white corundum fine powder 16-18%, alumina ultrafine powder 16-18%, Fine powder 3~4%, high-purity silicon powder 3~4%, binder 5~7%, water reducer 0.15~0.2%, organic fiber 0.08~0.1%, fused synthetic mullite with particle size >5mm and <8mm 8~10%, fused synthetic mullite with particle size >3mm and <5mm 16~17%, fused synthetic mullite with particle size >1mm and <3mm 20~21%, fused synthetic mullite with particle size <1mm 23~25%, stainless steel heat-resistant fiber 1~1.5%; (2) First, the No. 1 fine powder, binder, water reducing agent and organic fiber are uniformly mixed to obtain a No. 1 premix; (3) Adding aggregate No. 1 to premix No. 1 and mixing evenly to obtain premix No. 2; (4) adding stainless steel heat-resistant fiber to the No. 2 premix and mixing evenly to obtain a No. 3 premix; (5) Add water to the No. 3 premix and stir evenly to obtain the No. 1 castable. The amount of water added is 6-9% of the mass of the No. 3 premix; (6) Weighing a porous light mullite particle raw material, the porous light mullite particle raw material comprises mullite fine powder, silicon powder, alumina fine powder, fly ash, kaolin, PP particles with a particle size of 1-5 mm, a foaming agent, and 6 mm organic fiber, wherein the mass percentage of the porous light mullite particle raw material is as follows: the porous light mullite particle raw material comprises 26-40% of mullite fine powder, 10-16% of silicon powder, 20-34% of alumina fine powder, 8-12% of fly ash, 8-12% of kaolin, 5% of PP particles with a particle size of 1-5 mm, 1% of foaming agent, and 0.1-0.15% of 6 mm organic fiber; adding water to the porous light mullite particle raw material, stirring evenly, and pressing into blocks, wherein the amount of water added is 3-5% of the mass of the porous light mullite particle raw material, sintering at 1250° C. and re-crushing into porous light mullite particles; (7) Take lightweight raw materials: including No. 2 aggregate, No. 2 fine powder, binder, and water reducer. No. 2 aggregate includes porous lightweight mullite particles with a particle size of >5mm and <8mm, porous lightweight mullite particles with a particle size of >3mm and <5mm, porous lightweight mullite particles with a particle size of >1mm and <3mm, hollow alumina spheres with a particle size of >1mm and <3mm, and lightweight mullite with a particle size of <1mm. No. 2 fine powder includes synthetic mullite fine powder, alumina fine powder with an alumina content of 85%, and high-purity silicon powder. The weight percentage of the lightweight raw materials is: 5-10% porous light mullite particles with a particle size of >3mm and <5mm, 15-17% porous light mullite particles with a particle size of >3mm and <5mm, 10% porous light mullite particles with a particle size of >1mm and <3mm, 8-10% alumina hollow spheres with a particle size of >1mm and <3mm, 20-22% light mullite with a particle size of <1mm, 8-10% mullite fine powder, 12-15% alumina fine powder with an alumina content of 85%, 3-5% high-purity silicon powder, 8-12% binder, and 0.15-0.2% water reducer, and mix them evenly to obtain No. 4 premix; (8) Add water to the No. 4 premix and stir evenly to obtain the No. 2 castable. The amount of water added is 20-25% of the mass of the No. 3 premix; (9) Carry out lightweight layer construction: Pour No. 2 castable into the construction site, vibrate the construction site with a vibrating rod to remove air holes, and the thickness of the thinnest part should not be less than 70 mm, and then smooth it; (10) Adding metal reinforced grid frame: Lay the metal reinforced grid frame flat on the smooth surface of No. 2 castable; (11) Construction of heavy layer: After the light layer hardens, pour No. 1 castable onto the surface of the flat metal reinforced grid frame, add 7-10% of the mass of No. 1 castable with water, use a vibrating rod to vibrate and compact, and smooth it after reaching the required construction thickness; (12) Maintenance: Sprinkle water every hour to keep it moist, and maintain at room temperature for more than 24 hours.

2. The method for pouring a coke oven roof platform according to claim 1, characterized in that: The binder is high alumina cement.

3. The method for pouring a coke oven roof platform according to claim 1, characterized in that: The water reducer is a phosphate water reducer or a naphthalene water reducer.

4. The method for pouring a coke oven roof platform according to claim 1, characterized in that: The metal reinforced grid frame is connected by four metal sheets in a tic-tac-toe structure, and the tic-tac-toe structure is connected by S-shaped nails. The metal sheets are arranged horizontally and the S-shaped nails are arranged vertically.

5. The method for pouring a coke oven roof platform according to claim 1, characterized in that: The metal sheet material and the S-shaped nail are both made of 06Cr23Ni13 stainless steel.